Trabalho com significado e sentido de vida: um estudo com líderes empresariais - Azevedo, Andreia Magalhães (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2021)
What are the factors recognized by Portuguese business leaders for a meaningful work? In this article a sociological approach is presented that points out possible answers to this question. Starting from the problematization of work as central to human life, the research identifies and relates factors of meaning valued at work and in life, in the population considered. The results are analyzed in a professional connection model. It is proposed the reflection on the relevance of alignment in valued meaning factors, for human fulfillment.